Parental Involvement in Fostering Children's Learning Motivation - Jalaluddin, Jalaluddin; Mahardani, Rosita Arya; Sartika, Sartika (Universitas Hamzanwadi, 2024)
This qualitative research explores the pivotal roles of parents in motivating their children to learn. The study aims to (1) unravel the strategies employed by parents to motivate their children in learning, (2) identify challenges faced by parents in providing compelling motivation, and (3) propose solutions to address these parental difficulties. Employing a qualitative research design, this study focused on investigating parents and students in an Indonesian Elementary School as the participants. Data collection involved observation, interviews, and documentation. The findings reveal recurring difficulties parents and children face in the learning process. From the children's perspective, challenges include difficulty comprehending subject matter, lack of focus during learning sessions, reluctance to study, and excessive reliance on electronic gadgets. These challenges can be particularly daunting for parents, who also face their own obstacles. From the parental standpoint, obstacles include busy schedules, a lack of clarity regarding motivation, and familial issues. Understanding and empathizing with these challenges is crucial for devising effective solutions. This research contributes valuable insights into the dynamics of parent-child interactions related to education. Identifying challenges and proposing solutions is just the first step. It provides a foundation for future interventions that are urgently needed to enhance parental involvement in fostering children's learning motivation. The time to act is now.